2020
DOI: 10.1002/asi.24362
|View full text |Cite
|
Sign up to set email alerts
|

Information behavior and social control: Toward an understanding of conflictual information behavior in families managing chronic illness

Abstract: The relationship between information and control interests social scientists; however, much prior work has focused on organizations rather than families. Work on interactive information behaviors has also focused on organizations and on collaboration rather than conflict. Therefore, in families managing chronic illness, we investigated information behaviors in the context of health‐related social control and the impact of control on patient health behavior. We conducted a qualitative analysis of interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Proxy seekers used OHI to better understand someone else’s illness or to help themselves feel more empowered in their role as caregivers [ 49 , 64 , 65 , 67 ]. Several studies reported the sharing of information between caregiver and patient either directly by sending them a link or printout or indirectly by discussing the information found [ 49 , 50 , 57 , 60 , 64 , 68 ]. One study describes sharing and resharing the information among a social network so that it reaches a larger number of people [ 55 ] or so that a larger number of people are involved in making sense of the information [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proxy seekers used OHI to better understand someone else’s illness or to help themselves feel more empowered in their role as caregivers [ 49 , 64 , 65 , 67 ]. Several studies reported the sharing of information between caregiver and patient either directly by sending them a link or printout or indirectly by discussing the information found [ 49 , 50 , 57 , 60 , 64 , 68 ]. One study describes sharing and resharing the information among a social network so that it reaches a larger number of people [ 55 ] or so that a larger number of people are involved in making sense of the information [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…They used the information to change that person’s lifestyle; for example, mothers in 1 study cooked healthier food and encourage their families to walk together as a form of exercise [ 55 ]. In another study, the authors report that family members used the information to exert control on the patient, using techniques such as pushing or guilting [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently, the management of chronic disease involves a fundamental change in everyday behaviours with most of the burden falling outside of supervised healthcare environments [ 1 ]. A type-2 diabetes diagnosis, for example, requires significant lifestyle changes including ongoing self-management and self-awareness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, surrogate information seeking does not always lead to positive outcomes. Some people may use surrogate information seeking and information sharing to socially control their family members, which can negatively affect the relationship between the two parties (Brown & Veinot, 2020). Regardless outcomes, surrogate information seeking poses a challenge to surrogate seekers as they need to understand others' information needs and then seek information from various online sources, evaluate, and deliver relevant information.…”
Section: Introductionmentioning
confidence: 99%